2017
DOI: 10.1080/21622965.2016.1268960
|View full text |Cite
|
Sign up to set email alerts
|

Performance on tasks of visuospatial memory and ability: A cross-sectional study in 330 adolescents aged 11 to 20

Abstract: Cognitive functions mature at different points in time between birth and adulthood. Of these functions, visuospatial skills, such as spatial memory and part-to-whole organization, have often been tested in children and adults but have been less frequently evaluated during adolescence. We studied visuospatial memory and ability during this critical developmental period, as well as the correlation between these abilities, in a large group of 330 participants (aged 11 to 20 years, 55% male). To assess visuospatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
1
7
0
2
Order By: Relevance
“…Visuospatial ability, measured by the DOT, increases with age. The average increase in the DOT score per year corresponds to the findings reported in previous cross-sectional studies (Burggraaf et al, 2015(Burggraaf et al, , 2017. One reason why visuospatial abilities increase during childhood might be that visuospatial abilities can increase with, for instance, musical expertise training (Brochard, Dufour, & Despr es, 2004), certain types of sports (Moreau, Clerc, Mansy-Dannay, & Guerrien, 2012), or video game play (Cherney, 2008;Sanchez, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Visuospatial ability, measured by the DOT, increases with age. The average increase in the DOT score per year corresponds to the findings reported in previous cross-sectional studies (Burggraaf et al, 2015(Burggraaf et al, , 2017. One reason why visuospatial abilities increase during childhood might be that visuospatial abilities can increase with, for instance, musical expertise training (Brochard, Dufour, & Despr es, 2004), certain types of sports (Moreau, Clerc, Mansy-Dannay, & Guerrien, 2012), or video game play (Cherney, 2008;Sanchez, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…To assess the visuospatial ability of the participants, we used a slightly shorter variation of the Design Organization Test (DOT; Killgore et al, 2005;Killgore & Gogel, 2014). Our own previous research (Burggraaf et al, 2015(Burggraaf et al, , 2017 showed the usability of a slightly shorter variation of the DOT instead of the Block-Design test when determining the development of visuospatial ability during adolescence. An advantage of the DOT is that it takes only approximately 10 minutes to explain and administer, which is much faster than the Block-Design test.…”
Section: Visuospatial Ability Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the associations between parents' level of education and children's intelligence (Von Stumm & Plomin, 2015), and the association between age and performance on cognitive tests (Burggraaf, Frens, Hooge, & Van der Geest, 2018), we would test for confounders of success in ballet/music including age and the level of parental education.…”
Section: )mentioning
confidence: 99%